Fabrication of Ba Doped LaMnO3 Nanomaterials by Microwave Combustion Method - Tuyen, Nguyen Viet; Ha, Tran Thi; Hai, Pham Nguyen; Uyen, Tran Thi; Dinh, Nguyen Ngoc; Thu, Nguyen Thi Ha (VNU Journal of Science: Mathematics - Physics, 2020)
The major energy sources that human are relying on are fossil fuel and it is exhausted day by day. Furthermore, exploition and usage of fossil fuel also bring in many negative impacts on environmental polution. Solid oxide fuel cell (SOFC) has been considerred as a potential solution for such environmental and energy problems. Seeking a facile, cost and time saving process to synthesize Ba doped LaMnO 3 is very important for development of SOFC applications because it helps to reduce the cost of comercial SOFC. LaMnO 3 doped with Ba is more cost effective than Sr doped LaMnO 3 because less rare earth elements are used. At the same time, its conductivity is still good enough with an appropriate thermal expansion matched with those of other parts of SOFC based on ytrium stabilized zirconia (YSZ). In this paper, Ba doped LaMnO 3 nanoparticles (LBMO), a promissing material for making cathode of SOFC, were prepared by microwave combustion method. This material has many advantages.  Effect of the amount fuel in the combustion reaction on the products was studied by various methods such as: X-ray diffraction measurement, scanning electron microscopy, energy dispersive X-ray spectroscopy. The results showed that each doping rate requires an appropriate amount of fuel to obtain pure and crystalline product. The obtained LBMO nanoparticles are crystallined in hexagonal phase at doping ratio of 0.2 and orthohombic phase at doping ratio of equal or larger than 0.3.